Evaluating Risk Factors for Protein Energy Malnutrition in Severely Malnourished Children Admitted in a Tertiary Care Hospital (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Malnutrition the silent emergency is more clearly revealed its impact on children those who are the most vulnerable to suffer. Objective: The objective of the study was to evaluate the risk factors of protein energy malnutrition of severely malnourished children admitted in a Hospital. Methods: An open case–control study was carried out between June 2023 and November 2023 at the Pediatric Gastroenterology and Hepatology Unit of Bangladesh Shishu Hospital & Institute in Dhaka. As cases, the study comprised 50 hospitalized children with severe malnutrition, while 50 well-nourished children served as controls. An anthropometric assessment was carried out soon following admission. A semi-structured questionnaire was used to collect data, which included variables including age, gender, nutritional status, socioeconomic and sociodemographic characteristics and psychosocial history, as well as parents' monthly family income. At the outset of the study, demographic and nutritional information was gathered. Result: This present study showed majority of malnourished children were below 12 months of age more in male, came from urban slum from poor socioeconomic class and majority were partial immunized. Most of the mother and father were none educated and mothers were garments worker and fathers were day labor in case group. In case group 90% did not practice hand washing before feeding and 94% after defecation, 54% used tap water, 84% did not use save drinking water and 70% used Kancha latrine. In control group 92% practice hand washing before feeding and 62% after defecation, 86% used tap water and 78% used sanitary latrine. Sanitation and safe drinking water were poor in case group in comparison to control group. Conclusion: From the findings of the present study it can be concluded that poverty, illiteracy, immunization, poor sanitation, lack of safe drinking water, bottle feeding with dilute formula milk and poor hygienic situation are the important risk factors of severely malnourished children.J  Dhaka National Med. Coll. Hos. 2025; 31 (02): 17-23